Al-Quran dalam Diskursus Hedonisme: Analisis Kritis Ayat-ayat Hedonis dalam Tafsir Fi Zilail Quran Karya Sayyid Qutb - Fauziah, Wiwi; Anggraini, Tri Faizah (Contemporary Quran, 2022)
The flow of interpretation often becomes 'commonplace' when examining the dynamics of Qur'anic exegesis, particularly in the classical and medieval periods. Sayyid Qutb, in his work Tafsir fi Zilal al-Qur'an, is believed to incorporate a da'wah narrative aimed at disseminating a comprehensive understanding of Islamic law. His interpretation reflects the historical context and personal experiences of the Mufassir, which influenced his interpretative style. For instance, materialism and hedonism are seen as underlying factors that have led to certain interpretative perspectives, phenomena that remain prevalent in society today. Therefore, this study seeks to uncover the da'wah narrative in Sayyid Qutb's interpretation and explore his response to the phenomenon of a hedonistic lifestyle, specifically referring to QS. al-Hadid: 20, QS. al-An'am: 32, QS. al-Qasas: 32, and  QS. at-Takathur: 1-2. To achieve this, the research employs a qualitative methodology, utilizing content analysis as a data analysis tool. The study's findings reveal Sayyid Qutb's efforts to uphold Islamic reform by opposing life systems that marginalize Islamic values, such as materialism and hedonism. In Sayyid Qutb's perspective, hedonism is addressed through advocating for a balanced approach that harmonizes worldly pursuits with the values of the hereafter.